Metal–Organic Frameworks: Photosensitizer‐Anchored 2D MOF Nanosheets as Highly Stable and Accessible Catalysts toward Artemisinin Production (Adv. Sci. 11/2019). Issue 11 (4th June 2019) - Wang, Ying; Feng, Liang; Pang, Jiandong; Li, Jialuo; Huang, Ning; Day, Gregory S.; Cheng, Lin; Drake, Hannah F.; Wang, Ye; Lollar, Christina; Qin, Junsheng; Gu, Zhiyuan; et al.
Abstract : In article number1802059, Ying Wang, Liang Feng, Shuai Yuan, Hong‐Cai Zhou, and co‐workers report a stable and highly accessible 2D‐metal–organic framework (MOF) catalyst for artemisinin production. By introducing porphyrin‐based carboxylate ligands on the coordinatively unsaturated Zr sites in the MOF, the functionalized MOF nanosheet allows for enhanced accessibility of the catalytic sites, fast catalytic reaction kinetics and enhanced recyclability.